Charlie cook's favourite book - Donaldson, Julia; Scheffler, Axel (ill.) (London Macmillan, 2015)
Charlie Cook is reading a book about a pirate captain, who is reading a book about Goldilocks, who is reading about a knight, who is reading about a frog . . . From kings and queens to aliens and ghosts, there's something for everyone in Charlie's amazing book of adventure! Perfect for classroom use, Charlie Cook's Favourite Book Big Book is an extra-large edition.
Contains colourful illustrations.
Keywords: Children-Story